Is the bioaccessibility of minerals affected by the processing steps of juçara fruit (Euterpe edulis Mart.)? - Pupin, Letícia [UNESP]; Santos, Vívian da Silva; Santos Neto, João Paixão dos [UNESP]; De Fusco, Deborah Oliveira [UNESP]; Teixeira, Gustavo Henrique de Almeida [UNESP] (Elsevier, 2018)
The objective of this study was to verify if the processing steps of juçara fruit (Euterpe edulis Martius) affect mineral bioaccessibility using in vitro gastrointestinal digestion (IVG) followed by inductively coupled plasma optical emission spectrometry (ICP OES) analysis. The processing of the juçara fruit affected the content of calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), copper (Cu), and zinc (Zn), and their bioaccessibility. It was observed an increase in the content of all minerals after the pulp extraction and reduction in bioaccessibility. It was possible to determine the bioaccessibility with the use of the IVG method and ICP OES. The bioaccessibility of Mg, Fe, Mn, and Cu decreased in the last processing step (pulp extraction), with the exception of Ca and Zn that could not be determined.
Keywords: ICP OES; In vitro digestion; Minerals